(untitled) (Panauti Journal, 2025)
AI can help Nepal build a better future in human development and education. This review paper examines the transformative potential of artificial intelligence (AI) for human development and education in Nepal. Drawing on national policy documents, global reports, and academic studies, the review highlights AI’s applications across sectors including education, health, agriculture, finance, and disaster management, and its capacity to drive economic growth, social transformation, and human capital formation. In education, AI supports personalized learning, intelligent tutoring, predictive analytics, and digital assistants, contributing to inclusive and equitable access while advancing Sustainable Development Goal 4 (Quality Education). Despite these opportunities, Nepal faces challenges including policy gaps, limited infrastructure, low AI literacy among teachers, and ethical and data privacy concerns. Lessons from international experiences, notably China’s strategic digital investments, underscore the importance of stakeholder collaboration, faculty upskilling, and human-centered AI policies. The review concludes that integrating AI thoughtfully can enhance institutional efficiency, reduce inequalities, and strengthen Nepal’s capacity for socio-economic and educational transformation. Future research should explore AI-driven innovations in governance, health, and sustainable development, ensuring alignment with national priorities and global best practices. Integrating AI in Nepal’s education system can reduce inequalities and accelerate progress toward sustainable human development.